Glutathione transferase Omega 1‐1 (GSTO1‐1) modulates Akt and MEK1/2 signaling in human neuroblastoma cell SH‐SY5Y. Issue 7 (25th March 2019) - Saisawang, Chonticha; Wongsantichon, Jantana; Robinson, Robert C.; Ketterman, Albert J.
Abstract: In the human neuroblastoma SH‐SY5Y cell line, the glutathione transferase Omega 1‐1 (GSTO1‐1) appears to modulate Akt and MEK1/2 kinase activation. We observed a glutathionylation modification was involved in the activation of Akt but not MEK1/2. With the specific GSTO1‐1 inhibitor ML175, we show the enzyme activity of GSTO1‐1 is important for modulation as the inhibited GSTO1‐1 allowed activation of both Akt and MEK1/2. The inhibition of GSTO1‐1 showed a similar extent of activation of Akt and MEK1/2 as treatment by the endotoxin lipopolysaccharide. The GSTO1‐1 also either directly interacts with Akt and MEK1/2 or interacts with a protein complexed with Akt and MEK1/2 as both kinases coimmunoprecipitated with GSTO1‐1. The results suggest that GSTO1‐1 enzyme activity inhibits the activation of these two kinases to maintain basal levels. The possible regulation by GSTO1‐1 is of interest as both kinases have hundreds of potential downstream targets that are known to have contributions to various cellular processes including survival, growth, proliferation, and metabolism.